Hydrogenated Palm Fatty Acid Distillate as Raw Materials for Magnesium Stearate Alternatives - Dianika Lestari; Abdu Ravi Zakaria; Dwi Rokhmat Setiawan; Shelly Shelly; Melia Laniwati; Ardiyan Harimawan; Muhamad Insanu; Diky Mudhakir (Journal of Engineering and Technological Sciences, 2021)
Palm fatty acid distillate (PFAD) was used as raw material to produce solid lubricant, or anti-adherent, for confectionery or pharmaceutical products. To improve the degree of saturation, the PFAD was hydrogenated by using two methods: gaseous hydrogenation (GH) and catalytic transfer hydrogenation (CTH) using ammonium formate to produce hydrogenated PFAD (HPFAD). The HPFAD was saponified with MgO to produce magnesium salts of hydrogenated PFAD (Mg-HPFAD). The objective of this research was to investigate the effect of hydrogen concentration and reaction temperature on the iodine value of HPFAD and to investigate the characteristics of paracetamol tablets when using Mg-HPFAD as lubricant compared to commercial Mg-stearate. The HPFAD produced by CTH had a lower iodine value than the HPFAD produced by GH. The lowest iodine value was obtained after CTH using 3.6 M ammonium formate at 90°C. Paracetamol tablets with Mg-PFAD or Mg-HPFAD lubricant showed higher dissolution of active compounds with similar friability, frictiability, and hardness compared to paracetamol tablets with Mg-stearate.